PROBLEMS OF THE SOCIAL DIALOGUE DEVELOPMENT IN UKRAINE - SAMOLIUK, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The economic shock caused by the COVID-19 pandemic and the war situation in certain types of economic activity due to the destruction of the usual communication channels and the stoppage of employment in traditional workplaces contributed to the identification of SD as an essential tool for regulating social and labour relations. This paper examines three groups of factors that hinder the effective development of social dialogue in Ukraine. It was revealed that they are caused by the peculiarities of the business environment, the imperfection of state regulation and the underdevelopment of institutional support. It has been proven that today the question of the formation of representative bodies of subjects of social and labour relations capable of fully representing the collective interests of individual social groups and capable of carrying out a productive civilized social dialogue to resolve the most pressing issues and resolve conflicts remains open. There are given some reasons that negatively affect the process of institutionalization of the parties to the social dialogue (employers and employees) and limit their opportunities, in particular: public disappointment in the efficiency and effectiveness of trade unions, a decrease in the level of trust in them; weak organizational activity regarding attracting new members to the trade union, including due to the lack of an effective trade union information system; centralization and significant politicization of the processes of creation and activity of employers' associations; inconsistency of legislation, modern challenges, in particular, failure to take into account the real structure of enterprises in terms of size; unformed representation of employers at the level of individual industries and others. The article also argues the need to develop and implement a systematic and effective communication strategy based on digital technologies to expand cooperation and facilitate communications between employers, trade unions, and relevant state bodies to ensure tripartite dialogue.
Keywords: social dialogue; social partners; trade union; employers' association; institutional support